A Persistência Da Imagem, Entre Os Ex-Votos E As Xilogravuras: A Constituição De Uma Tradição - Alcantara, Andreia De [UNIFESP] (2018)
The Purpose Of This Work Is To Analyse Recurring Practices, Themes And Imagine Son Both, The Art Of The Ex-Votos (Devotional Art Pieces Made And Given By A Faithful Person To A Certain Patron Saint To Thank For A Granted Grace), From The State Of Minas Gerais, And The Popular Engraving Art Made By People From The Northeast Region Of Brazil. To Do So, It Was Used Ex-Votos Material Dating Back To The Eighteenth, Nineteenth And Early Twentieth Centuries Painted In Minas Gerais State, From Two Collections Of Iphan (Instituto Do Patrimônio Hístórico E Artístico Nacional " Minas Gerais Branch) And A Private Collection Of Contemporary Engraving North-Eastern Artists, From Map (Museu De Arte De Diadema " São Paulo"S District). This Analysis Intends To Seek The Origins Of The"Popular Art" Concept; To Show, By Studying The Dialog Between Both Arts In Time And Space, A Tradition Pathway; To Analyse The Pattern Of Transmitting And Receiving Art, Likewise,Analyseformal Repetition Using Elements Eventually From Erudite Met